Access and Scholarly Use of Web Archives. Issue 1 (1st August 2014) - Hockx-Yu, Helen
Abstract : This article provides an overview of current access arrangements of web archives. Using data from a user survey of the UK Web Archive, it attempts to analyse the reasons for limited scholarly use of web archives. It also examines the key characteristics of scholarly use of digital sources and translates these into a set of requirements for web archives. It discusses how current web archives fail to meet the evolving scholarly requirements, offering some thoughts on a way forward, from the perspective of a national research library and a web archiving service provider.